Broadband and productivity: Structural estimates for Germany - Tomaso Duso; Mattia Nardotto; Alexander Schiersch (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
We study the impact of broadband availability on firms' total factor productivity (TFP) using German firm-level data between 2010 and 2015. We adopt a control function approach to causally identify and separately estimate productivity for 46 two-digit manufacturing and service sectors. Over the sample period, broadband availability, measured by 16 Mbps transmission rates, more than doubled in German municipalities. While this increased broadband availability has almost no effect on firms' productivity in manufacturing, it significantly increases TFP in most service sectors. Yet, the size of the effect is heterogenous across industries.
Keywords: D24; D22; J24; O14; O22; O33; 330; broadband internet; productivity; firm-level data